Les évaluations nationales de CM2 : modes de passation et spécificités disciplinaires - Elisabeth Menouar; Daniel Bart (Recherches en Éducation)
This article presents research conducted on national assessments in French and Mathematics at primary school and more precisely on how they are implemented in classrooms. On the basis of different classroom observations, conversations with teachers and the study of official documents, we analyze how these assessments are implemented and highlight the characteristics proper to each discipline. Our analysis shows the inconstancy in the guidelines applied to tests, the variability of the practices in terms of instructions and the tensions related to time management during the sessions. Our conclusions lead to methodological questions and research opportunities on the process of the institutional assessments.